2003
DOI: 10.1046/j.1365-2427.2003.01009.x
|View full text |Cite
|
Sign up to set email alerts
|

Particulate fatty acids in two small Siberian reservoirs dominated by different groups of phytoplankton

Abstract: SUMMARY 1. We studied the composition of fatty acids (FAs) in the seston from two small freshwater reservoirs (Bugach and Lesnoi) with distinct periodicity of domination by cyanobacteria and eukaryotic algae during the growth season. 2. The diatoms in the both reservoirs were characterised by a high content of 14:0 and C16 unsaturated acids, whereas that of the essential FA 20:5ω3 [eicosapentanoic acid (EPA)] was low. The correlation between this polyunsaturated FA (PUFA) and diatom biomass was not significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 37 publications
1
25
0
Order By: Relevance
“…PUFA were represented by the sum of x-3 acids: 18:3x-3, 18:4x-3, 20:3x-3, 20:4x-3, 20:5x-3, 22:5x-3 and 22:6x-3. The same was done for the non-essential C16-PUFA, which were represented by the sum of 16:2x-4, 16:3x-4, and 16:4x-1, characteristic of diatom algae, and of 16:2x-6, 16:3x-3, and 16:4x-3, characteristic of green algae (Ahlgren et al 1992;Sushchik et al 2003a). …”
Section: Calculations Of Pufa Productionmentioning
confidence: 99%
“…PUFA were represented by the sum of x-3 acids: 18:3x-3, 18:4x-3, 20:3x-3, 20:4x-3, 20:5x-3, 22:5x-3 and 22:6x-3. The same was done for the non-essential C16-PUFA, which were represented by the sum of 16:2x-4, 16:3x-4, and 16:4x-1, characteristic of diatom algae, and of 16:2x-6, 16:3x-3, and 16:4x-3, characteristic of green algae (Ahlgren et al 1992;Sushchik et al 2003a). …”
Section: Calculations Of Pufa Productionmentioning
confidence: 99%
“…Commonly, 20:5x3 and x7, x4 and x1 C16 PUFAs are considered as diatom markers (Brett et al 2009). However, Sushchik et al (2004) have demonstrated that summer diatom populations can be low in PUFA compared with the spring ones, while 14:0 and 16:1x7 together are good predictors of both summer and spring populations of diatoms (Sushchik et al 2003a). Diatoms are reported in both lakes in summer (Gaevsky et al 2002), with lower occurrence in L. Shira, that is in good accord with the lower percentages of FATM 14:0 and 16:1x7, observed in our study.…”
Section: Fatm In Tag and Feeding Experiments As Indicators Of The Diementioning
confidence: 99%
“…However, it is known that 18:3x3 is also synthesized by Cyanobacteria, especially filamentous species (Gugger et al 2002). Moreover, Sushchik et al (2003a) have shown in a freshwater reservoir that 18:3x3 indicates dominance of both green algae and Cyanobacteria. We have noted that in summer period Cyanobacteria Lyngbya contorta, a non-identified small-sized cyanobacterial species, and green algae of Dictyospherium genus dominate phytoplankton in Lake Shira (Gaevsky et al 2002).…”
Section: Fatm In Tag and Feeding Experiments As Indicators Of The Diementioning
confidence: 99%
“…Its surface area is 0.32 km 2 , and its maximum depth is 7 m, and the mean depth is~2 m. Mean seasonal concentrations of dissolved inorganic phosphorus in 2002, 2003 and 2004 were 0.014 mg l )1 , 0.005 mg l )1 and 0.008 mg l )1 , respectively, and mean concentrations of NH 4 -N were 0.163 mg l )1 , 0.254 mg l )1 and 0.221 mg l )1 , respectively. Detailed descriptions of the Reservoir are given elsewhere (Sushchik et al 2003a(Sushchik et al , 2004.…”
Section: The Study Sitementioning
confidence: 99%
“…It should be noted, that while initially the core role of EPA in nutrition of some zooplankton species (population) has been emphasized, we consider also the sum of x3-PUFA, like in some other studies (Park et al 2002;Von Elert 2004), because recently there is strong evidences has been obtained concerning the importance of diverse x3 species for zooplankton growth, such as a-linolenic, 18:3x3 (Wacker and Von Elert 2001;Sushchik et al 2003a), stearidonic, 18:4x3, (Ravet et al, 2003) and eicosatetraenoic, 20:4x3 (Becker et al 2004) acids. We found Sx3-PUFA better related with the whole elemental composition (stoichiometry) of seston, than any single PUFA species.…”
Section: Ranges Of Concentrations Of Poc In Bugachmentioning
confidence: 99%